Synthesis of nopol over MCM-41 catalysts (2002)
ABSTRACT: MCM-41 was found to be an active heterogeneous catalyst for the synthesis of nopol by the Prins condensation of bpinene and paraformaldehyde, but Sn-MCM-41 in which Sn has been grafted on MCM-41 by chemical vapor deposition is far more active and combines high efficiency and recyclability.